2010
DOI: 10.1016/j.paid.2010.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of mental health and illness in substance abuse patients

Abstract: This study examined the latent structure of a number of measures of mental health (MH) and mental illness (MI) in substance use disorder outpatients to determine whether they represent two independent dimensions, as Keyes (2005) found in a community sample. Seven aspects of MI assessed were assessed -optimism, personal meaning, spirituality/religiosity, social support, positive mood, hope, and vitality. MI was assessed with two measures of negative psychological moods/ states, a measure of antisociality, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Keyes (2005, 2007, 2009) has argued that MH is a distinctive dimension from mental illness (MI) and in a confirmatory factor analyses (CFA) of MH and MI (Keyes, 2005) measures found them to be relatively independent dimensions. A recent study by our group (Alterman, Cacciola, Ivey, Coviello, Lynch, Dugosh, & Habing, submitted paper) in outpatients with substance use disorders (SUD), using both exploratory factor analysis (EFA) and CFA, obtained findings consistent with this conclusion. Importantly, literature has shown that MH attributes such as optimism, positive mood, and social networks have important positive implications for physical illness independent of the effects of MI states such as depression, anxiety, or hostility (Carver, et al, 2009; Cohen & Janicki-Deverts, 2009; Pressman & Cohen, 2005; Taylor & Stanton, 2007).…”
supporting
confidence: 60%
“…Keyes (2005, 2007, 2009) has argued that MH is a distinctive dimension from mental illness (MI) and in a confirmatory factor analyses (CFA) of MH and MI (Keyes, 2005) measures found them to be relatively independent dimensions. A recent study by our group (Alterman, Cacciola, Ivey, Coviello, Lynch, Dugosh, & Habing, submitted paper) in outpatients with substance use disorders (SUD), using both exploratory factor analysis (EFA) and CFA, obtained findings consistent with this conclusion. Importantly, literature has shown that MH attributes such as optimism, positive mood, and social networks have important positive implications for physical illness independent of the effects of MI states such as depression, anxiety, or hostility (Carver, et al, 2009; Cohen & Janicki-Deverts, 2009; Pressman & Cohen, 2005; Taylor & Stanton, 2007).…”
supporting
confidence: 60%
“…This model was replicated in several studies that confirmed the latent structure of the indicators of well-being within the psychological context (Gallagher, Lopez, & Preacher, 2009;Keyes, 2002Keyes, , 2005aKeyes, , 2007Keyes, Shmotkin, & Ryff, 2002;Linley, Maltby, Wood, Osborne, & Hurling, 2009). The discriminant validity of the indicators of positive mental health relative to the indicators of psychopathology was assessed with exploratory and confirmatory factor analyses (Alterman et al 2010;Keyes, 2005a;Massé et al, 1998;Peter, Roberts, & Dengate 2011;Ryff & Singer, 1998;Weich et al, 2011;Westerhof & Keyes, 2010;Wilkinson & Walford, 1998). The application of both techniques showed that the full set of indicators is better represented by a model with two oblique factors instead of models that are unidimensional and have two orthogonal factors.…”
mentioning
confidence: 80%
“…Findings from a diverse set of studies and populations support Keyes' (2002Keyes' ( , 2005a argument for the dual continua model: one continuum indicating the presence and absence of positive mental health, the other indicating the presence and absence of mental illness symptoms such as depression and anxiety (Alterman, et al, 2010;Keyes, et al, 2008;Keyes, 2009a;Westerhof & Keyes, 2008. In the Midlife in the United States (MIDUS) sample, for example, the latent factors of mental illness -measured with past year MDE, panic attacks and generalized anxiety disorder -and mental health correlated (r ¼ À0.53), meaning only 28.1% of their variance is shared (Keyes, 2005a).…”
Section: Introductionmentioning
confidence: 98%